The Oxford encyclopedia of maritime history - Hattendorf, John B. 1941- (Oxford University Press, 2007)
"The Encyclopedia covers the entire history of seafaring, from ancient Egyptian shipbuilders to the nuclear submarines and supertankers of today. Over nine hundred articles written by leading historians examine all aspects of maritime history, including naval history, shipbuilding, biographies of major figures, navigation and scientific instrumentation, maritime art and literature, commerce and economics, and international law. Placing maritime affairs in their larger historical context, the Encyclopedia shows how seafaring has both reflected and influenced the major economic, cultural, military, and political developments in world history"--title screen.